2018
DOI: 10.1093/gerona/gly149
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Multimorbidity With Preclinical AD Stages and SNAP in Cognitively Unimpaired Persons

Abstract: Multimorbidity was associated with biomarker combinations that included neurodegeneration with or without elevated amyloid deposition (ie, A-N+, A+N+). The associations should be validated in longitudinal studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 44 publications
(62 reference statements)
0
17
0
Order By: Relevance
“…More recent clinical studies have demonstrated biomarker evidence of ‘suspected non-Alzheimer’s disease pathophysiology’ (SNAP) causing amnestic type cognitive impairment with substantial hippocampal atrophy but lacking detectable amyloid-β amyloidosis (Caroli et al , 2015; Burnham et al , 2016; Jack et al , 2016, 2017; Abner et al , 2017; Wisse et al , 2018). For example, the evaluation of 1535 participants in the Mayo Clinic Study of Aging showed significantly greater prevalence of SNAP compared with preclinical Alzheimer’s disease, and multimorbidity was increased in SNAP (odds ratio 2.16) (Vassilaki et al , 2018). LATE is probably an important contributor in this group of subjects (see below).…”
Section: Introductionmentioning
confidence: 99%
“…More recent clinical studies have demonstrated biomarker evidence of ‘suspected non-Alzheimer’s disease pathophysiology’ (SNAP) causing amnestic type cognitive impairment with substantial hippocampal atrophy but lacking detectable amyloid-β amyloidosis (Caroli et al , 2015; Burnham et al , 2016; Jack et al , 2016, 2017; Abner et al , 2017; Wisse et al , 2018). For example, the evaluation of 1535 participants in the Mayo Clinic Study of Aging showed significantly greater prevalence of SNAP compared with preclinical Alzheimer’s disease, and multimorbidity was increased in SNAP (odds ratio 2.16) (Vassilaki et al , 2018). LATE is probably an important contributor in this group of subjects (see below).…”
Section: Introductionmentioning
confidence: 99%
“…Certain chronic medical conditions, including type 2 diabetes (T2DM), hypertension, coronary artery disease, and depression, are established risk factors for cognitive decline (Artero et al, 2008;Vicini Chilovi et al, 2009;Li et al, 2012;Roberts and Knopman, 2013;Imtiaz et al, 2014;Johnson et al, 2015;Vassilaki et al, 2015;Fan et al, 2017). These conditions are also common in multimorbidity (defined as at least two comorbid conditions) in older adults, which may also be associated with biomarkers of the preclinical AD stages (Sperling et al, 2011;Jack et al, 2014;Sperling et al, 2014) and suspected non-amyloid pathophysiology (Jack et al, 2016;Vassilaki et al, 2019), even before clinically detectable cognitive decline becomes apparent. Not only is there an increase in the prevalence of comorbidities among patients at risk of AD, but multimorbidity, a distinctive hallmark of aging and potentially a clinical marker of accelerated aging (Fabbri et al, 2015), is also associated with increased risk of cognitive impairment (Palmer et al, 2007;Vassilaki et al, 2015;Santiago and Potashkin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As expected, only a small minority of patients with MCI and an even smaller subgroup of cognitively unimpaired persons exhibited abnormal scores on these scales, although abnormal scores have been associated with higher odds of being A+ and even higher chances of being N+. Therefore, not only subtle cognitive impairment appears to be in accordance with the asymptomatic stage of AD, but also subtle functional impairment at predementia stages . This would result in a slight modification of the biomarker model previously proposed from members of this group as shown in Figure .…”
mentioning
confidence: 83%
“…During the course of AD, the extent of impairment in both cognitive abilities and in activities of daily living (ADLs), also referred to as functional abilities, is used to define the clinical syndrome. The article in this issue of JAGS by Dr. Vassilaki and colleagues of the Mayo Clinic in Rochester, Minnesota, provides further evidence that there is no sharp demarcation of presence vs absence of impaired ADLs between the different clinical stages of AD, but rather a continuum of gradually increasing ADL impairment during the course of the disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation